Evaluating a National Anti-Firearm Law and Estimating the Causal Effect of Guns on Crime - Daniel Cerqueira; Jo\~ao de Mello (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2013)
We report two results. First, we evaluate the impact of a nationwide anti-firearm legislation passedby the Brazilian Congress in December 2003 (Estatuto do Desarmamento, henceforth ED). Our identificationstrategy hinges on the hypothesis that the law had stronger impact in places where gun prevalence washigher in the baseline. We find evidence that homicides (reduced form) and firearms prevalence(mechanism or first-stage) dropped faster in places with higher gun prevalence after the 2003. Using ourpreferred estimates, the ED saved between 2,000 and 2,750 lives from 2004 through 2007 in cities withmore than 50,000 inhabitants in the state of S\~ao Paulo. Second, assuming the ED causes homicide onlythrough its impact on firearms prevalence, we recover a causal estimate of the impact of firearms onhomicides. One standard deviation in the prevalence of firearms reduces homicides by quarter of astandard deviation. We find no impact of both ED and firearms on property crime in general or onrobberies.
Keywords: K42; 330; Gewalt; Kriminalitätsökonomik; Waffenrecht; Brasilien